Innovative Synoptic Reporting With Seven-Point Sampling Protocol to Improve Detection Rate of Microvascular Invasion in Hepatocellular Carcinoma - Liao, Bing; Liu, Lijuan; Wei, Lihong; Wang, Yuefeng; Chen, Lili; Cao, Qinghua; Zhou, Qian; Xiao, Han; Chen, Shuling; Peng, Sui; Li, Shaoqiang; Kuang, Ming (Frontiers in Oncology, 2021)
Pathological MVI diagnosis could help to determine the prognosis and need for adjuvant therapy in hepatocellular carcinoma (HCC). However, narrative reporting (NR) would miss clinical relevant information and non-standardized sampling would underestimate MVI detection. Our objective was to explore the impact of innovative synoptic reporting (SR) and seven point sampling (SPRING) protocol on microvascular invasion (MVI) rate and patient outcomes. In retrospective cohort, we extracted MVI status from NR in three centers and re-reviewed specimen sections by SR recommended by the College American Pathologists (CAP) in our center. In prospective cohort, our center implemented the SPRING protocol and external centers remained traditional pathological examination. MVI rate was compared between our center and external centers in both cohorts. Recurrence free survival (RFS) before and after implementation was calculated by Kaplan-Meier method and compared by the log-rank test. In retrospective study, we found there was no significant difference in MVI rate between our center and external centers (10.3% (115/1112) VS 12.4% (35/282), P=0.316). In our center, SR recommended by CAP improved the MVI detection rate from 10.3% to 38.6% (P<0.001). In prospective study, the MVI rate in our center under SPRING was significantly higher than external centers (53.2% VS 17%, P<0.001). RFS of MVI (-) patients improved after SPRING in our center (P=0.010), but it remained unchanged in MVI (+) patients (P=0.200). We conclude that the SR recommended by CAP could help to improve MVI detection rate. Our SPRING protocol further improved the MVI rate and optimized prognostic stratification for HCC patients.